Photocatalytic hydrogen evolution from water based on Zn–terpyridine 2D coordination nanosheets. Issue 45 (10th November 2022) - Xiang, Shuo; Khan, Arshad; Zhou, Zeyan; He, Bingling; Wang, Xin; Wang, Binju; Weng, Qunhong
Abstract : A zinc bis-terpyridine coordination nanosheet (Zn–Typ CONASH) is designed and shows a reduced optical band gap of 1.70 eV and impressive photocatalytic hydrogen evolution activity of 11.84 mmol g −1 h −1 . Abstract : Green hydrogen is an ideal and zero-pollution fuel that can be obtained using solar and other renewable energies. The efficient photocatalytic production of hydrogen mainly relies on the development of high-performance photocatalysts. In this work, we report the synthesis and photocatalytic hydrogen evolution application of a 2D coordination nanosheet (CONASH) constructed from bis-terpyridine ligands (Tpy) and Zn ions, which revealed an optical bandgap of 1.70 eV and exhibited excellent photocatalytic hydrogen-production performances of 3.10 mmol h −1 g −1 and 11.84 mmol g −1 h −1 under N2 and CO2 atmospheres, respectively. Such high photocatalytic hydrogen evolution rates are among the top tier in noble metal-free coordination complexes, providing a new way for designing hydrogen evolution photocatalysts based on highly structure- and band-adjustable 2D CONASHs.